2014
DOI: 10.1186/1475-2867-14-51
|View full text |Cite
|
Sign up to set email alerts
|

The ATRA-induced differentiation of medulloblastoma cells is enhanced with LOX/COX inhibitors: an analysis of gene expression

Abstract: BackgroundA detailed analysis of the expression of 440 cancer-related genes was performed after the combined treatment of medulloblastoma cells with all-trans retinoic acid (ATRA) and inhibitors of lipoxygenases (LOX) and cyclooxygenases (COX). The combinations of retinoids and celecoxib as a COX-2 inhibitor were reported to be effective in some regimens of metronomic therapy of relapsed solid tumors with poor prognosis. Our previous findings on neuroblastoma cells using expression profiling showed that LOX/CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…F9-induced cell death is also significantly higher than that observed with CXB-loaded PEGylated liposomes by Erdo g et al [72], who demonstrated that CXB-loaded PEGylated liposomes reduced the viability of HT-29 cells by about 0, 35 and 45% after 24, 48 and 72 h of incubation using a final liposomal CXB concentration of 100 µM (higher than our concentration of 89.15 µM). Despite the fact that CXB has been reported by many researchers to inhibit the growth of HepG2 [73] and Daoy cells [74], we believe we are the first to show the effects of CXB nanoparticles on these two cell lines. The significantly higher cytotoxicity observed with F9 than with F14 in the three cell lines suggests that Tween 80-stabilized SLN increases CXB cytotoxicity more than Cremophor EL-stabilized SLN, however the mechanism is unknown.…”
Section: Discussionmentioning
confidence: 62%
“…F9-induced cell death is also significantly higher than that observed with CXB-loaded PEGylated liposomes by Erdo g et al [72], who demonstrated that CXB-loaded PEGylated liposomes reduced the viability of HT-29 cells by about 0, 35 and 45% after 24, 48 and 72 h of incubation using a final liposomal CXB concentration of 100 µM (higher than our concentration of 89.15 µM). Despite the fact that CXB has been reported by many researchers to inhibit the growth of HepG2 [73] and Daoy cells [74], we believe we are the first to show the effects of CXB nanoparticles on these two cell lines. The significantly higher cytotoxicity observed with F9 than with F14 in the three cell lines suggests that Tween 80-stabilized SLN increases CXB cytotoxicity more than Cremophor EL-stabilized SLN, however the mechanism is unknown.…”
Section: Discussionmentioning
confidence: 62%
“…The mechanism target by this novel combination was cell proliferation, angiogenesis, and apoptosis for its anti-neoplastic effect (Paukovcekova et al 2020). The mechanism for the anti-neoplastic effect was further studied and even reported the synergistic effect of CA on ATRA in medulloblastoma cell lines (Chlapek et al 2014). These results warrant the scope of testing such a combination in the preclinical and clinical setup (Martinez-outschoorn et al 2017).…”
Section: Caffeic Acid and All-trans-retinoic Acid (Atra) In Cancermentioning
confidence: 99%
“…The capability of retinoids to induce cell differentiation of transformed cells was confirmed on various tumor types including promyelocytic leukemia [ 7 ], NBL [ 8 ], choriocarcinoma [ 9 ], and teratocarcinoma [ 10 ]. For example, the differentiating effects of retinoids encompass the increased expression of cell surface differentiation markers in myeloid leukemia cells [ 11 ], alterations in cell morphology and formation of neurite extensions in NBL [ 12 ], and growth inhibition and typical changes in gene expression in NBL and medulloblastoma cells [ 12 , 13 , 14 ].…”
Section: Retinoids As Inducers Of Cell Differentiationmentioning
confidence: 99%